2023
DOI: 10.1371/journal.pone.0277006
|View full text |Cite
|
Sign up to set email alerts
|

MiR-942-5p inhibits tumor migration and invasion through targeting CST1 in esophageal squamous cell carcinoma

Abstract: Introduction Cysteine Protease Inhibitor 1 (CST1), a cystatin superfamily protein with the effect on the inhibition of cysteine protease activity, is reported to be involved in the development of many malignancies. MiR-942-5p has been demonstrated its regulatory effects on some malignancies. However, the roles of CST1 and miR-942-5p on esophageal squamous cell carcinoma (ESCC) are still unknown up to now. Methods The expression of CST1 in ESCC tissues was analyzed by TCGA database, immunohistochemistry, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Besides, CST1 was found to promote gastric cancer by mediating Wnt/β-catenin/TCF signaling as a downstream effector of transcription factor TCF [33] . Encouringly, CST1 has also been shown its oncogenic potential on ESCC development by our pilot study, manifested as the aberrantly high expression and effect of CST1 on cell migration and invasion by the MEK/ERK signaling pathway in ESCC [30] . Therefore, we further made a comprehensive survey for the potential mechanism of CST1 on ESCC development by performing the transcriptome sequencing for ESCC cell with CST1 knockdown, and surprisingly discovered that the differential genes were closely related to the regulation of cell metabolic processes and mitochondrial respiratory chain-related oxidoreductase activity, and signi cantly enriched in metabolic and tumor-related signaling pathways, suggesting that CST1 might be involved in mediating mitochondrial OXPHOS of ESCC cells.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Besides, CST1 was found to promote gastric cancer by mediating Wnt/β-catenin/TCF signaling as a downstream effector of transcription factor TCF [33] . Encouringly, CST1 has also been shown its oncogenic potential on ESCC development by our pilot study, manifested as the aberrantly high expression and effect of CST1 on cell migration and invasion by the MEK/ERK signaling pathway in ESCC [30] . Therefore, we further made a comprehensive survey for the potential mechanism of CST1 on ESCC development by performing the transcriptome sequencing for ESCC cell with CST1 knockdown, and surprisingly discovered that the differential genes were closely related to the regulation of cell metabolic processes and mitochondrial respiratory chain-related oxidoreductase activity, and signi cantly enriched in metabolic and tumor-related signaling pathways, suggesting that CST1 might be involved in mediating mitochondrial OXPHOS of ESCC cells.…”
Section: Discussionmentioning
confidence: 68%
“…Considering the effect of CST1 on the migration and invasion of ESCC cells observed in our pilot study [30] , we made a comprehensive survey for the potential mechanism of CST1 on ESCC development by performing the transcriptome sequencing for ESCC cell line KYSE150 with CST1 knockdown by DESep2 software (Fig 1A). As a result, a total of 2452 differential genes were obtained, including 1181 genes increased and 1271 genes decreased (Fig 1B ); by Gene ontology (GO) function and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis, the differential genes were shown to be closely related to the regulation of cellular metabolic processes and mitochondrial respiratory chain-related oxidoreductase activity, and signi cantly enriched in metabolic and tumorrelated signaling pathways (Fig 1C, D), suggesting that CST1 might be involved in regulating mitochondrial OXPHOS of ESCC cells.…”
Section: Cst1 Regulates Oxphos In Escc Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…We suspect that the lack of repeat sequencing and the small sample size are possible reasons. However, after conducting a thorough search of online databases and reviewing multiple studies, it was determined that CST1 may serve as a reliable indicator for early diagnosis and prognosis of ESCC ( 13 , 24 26 ). We have tried several commercial ELISA kits, performing not as expected.…”
Section: Discussionmentioning
confidence: 99%
“…The miRs are small non-coding RNAs that regulate multiple gene expressions and control cellular processes, including cell cycle, migration, invasion, and extravasation. Recent studies have reported that miRs play an important role in HNSCC disease development and progression [36][37][38][39]. The therapeutic measures that can edit miRs' function have been recognized as an exciting new area of drug development.…”
Section: Discussionmentioning
confidence: 99%